In vivo photodynamic inactivation of Candida albicans using chloro‐aluminum phthalocyanine. (28th March 2016) - Carmello, JC; Alves, F; Ribeiro, APD; Basso, FG; de Souza Costa, CA; Tedesco, AC; Primo, FL; Mima, EG; Pavarina, AC
Abstract : This study evaluated the photoinactivation of Candida albicans in a murine model of oral candidiasis using chloro‐aluminum phthalocyanine (ClAlP) encapsulated in cationic nanoemulsions (NE) and chloro‐aluminum phthalocyanine (ClAlP) diluted in DMSO (DMSO) as photosensitizer (PS). Seventy‐five 6‐week‐old female Swiss mice were immunosuppressed and inoculated with C. albicans to induce oral candidiasis. PDT was performed on the tongue by the application of the photosensitizers and LED light (100 J cm −2 –660 nm). Twenty‐four hours and 7 days after treatments, microbiological evaluation was carried out by recovering C. albicans from the tongue of animals (CFU ml −1 ). Then, mice were sacrificed and the tongues were surgically removed for histological and biomolecular analysis of pro‐ and anti‐inflammatory cytokines. Data were analyzed by ANOVA followed by Tukey's post hoc test. ClAlP‐NE‐mediated PDT reduced 2.26 log10 of C. albicans recovered from the tongue when compared with the control group (P−L−) ( P  < 0.05). PDT did not promote adverse effects on the tongue tissue. Seven days after treatment, all animals were completely healthy. In summary, PDT mediated by chloro‐aluminum phthalocyanine entrapped in cationic nanoemulsions was effective in reducing C. albicans recovered from the oral lesions of immunocompromised mice.